The failure of agrarian capitalism : agrarian politics in the UK, Germany, the Netherlands, and the USA, 1846-1919 - Koning, Niek, 1948- (Routledge, 1994)
Agriculture is a highly sensitive industry. Throughout their history, national governments have intervened in and protected their agricultural sectors. The problems of competition in agriculture have been continually illustrated by disagreement over the European Community's Common Agricultural Policy (CAP) and, more recently, by attempts to reform farming policy in the last round of the GATT negotiations. The Failure of Agrarian Capitalism presents a comparative analysis of in agarian policies in the UK, Germany, the Netherlands and the USA from 1846-1919.